Impact of Digitalization of “Agriculture Marketing in India (International Journal of Food and Nutritional Sciences, 2022)
The agricultural sector, constituting a significant portion of India's economy, stands at the threshold of a transformative era driven by digitalization. This study delves into the profound impact of digital technologies on agriculture marketing practices across the Indian landscape. Through a multi-faceted research approach, combining comprehensive literature reviews, interviews with key stakeholders, and analysis of digital adoption trends, this study seeks to illuminate the dynamic shifts and emerging paradigms. The advent of digital platforms, mobile applications, and e-commerce channels has ushered in a new era of accessibility and efficiency in agriculture marketing. Farmers, once constrained by geographical limitations, now have unprecedented access to a wider consumer base, enabling them to transcend traditional market boundaries. This study meticulously examines the extent to which digitalization has streamlined supply chains, reduced information asymmetry, and empowered agricultural producers in the marketing process. Furthermore, this research places a critical lens on the socio-economic implications of digitalization. It probes the inclusivity of these technological advancements, ensuring that marginalized and smallholder farmers are not left behind in this digital revolution. Additionally, the study considers the resilience of these digital systems in the face of variable environmental conditions, acknowledging the need for adaptable solutions. The findings of this study offer a comprehensive understanding of the transformative potential of digitalization in agriculture marketing. From enhancing market access for farmers to promoting sustainability and transparency, the implications are far-reaching. As India navigates this digital terrain, this study provides valuable insights for policymakers, practitioners, and stakeholders seeking to harness the full potential of digital technologies in agriculture marketing.